Australian Indigenous Employability Education and Entrepreneurship: Exploring the Issues in a Compendium of Case Studies - Pearson, Cecil A. L.; Burgess, John; Dayaram, Kandy (2015)
Foreword. Ch. 1 Introduction – Cecil A. L. Pearson, John Burgess & Kantha Dayaram. Ch. 2 Brokering Indigenous Employment at a Remote Community in Northern Australia – Cecil A. L. Pearson & Sandra Daff. Ch. 3 Cultural Influences on Learning and Development Initiatives in Indigenous Australia – Cecil A. L. Pearson, Gayili Yunupingu-Marika & Sandra Daff. Ch. 4 Mining as the Catalyst for the Employment of Indigenous People in Social Ventures – Cecil A. L. Pearson & Klaus Helms. Ch. 5 Maintaining Core Business and Key Drivers in Mining: Indigenous Partnerships Releasing Value Through Recognising Difference – Hamish Morgan, Guy Singleton & Maria Fay Rola-Rubzen. Ch. 6 Indigenous Leadership in Practice: Context and Culture – Kantha Dayaram & Maria Fay Rola-Rubzen. Ch. 7 Aboriginal and Torres Strait Islander Art and its Place in the Global Art Market – Tim Acker. Ch. 8 Background to Aboriginal and Torres Strait Islander Art and the Art Industry – Kim Petersen & Susan Congreve. Ch. 9 Cultural Clashes as Impediments to Australian Indigenous Research – Cecil A. L. Pearson & John Burgess. Profiles of Contributors. References.